Phytochrome B influences in - Vitro shoot regeneration in arabidopsis thaliana (L.) heynh - Ezura, H; Higashi, K; Harberd, N (1999)
The effects of phyA and phyB mutations on shoot bud regeneration in Arabidopsis thaliana have been studied. The phyB mutant showed a significantly lower frequency of shoot bud regeneration than did the wild-type, indicating a role for phytochrome B in the regulation of in-vitro shoot bud regeneration. Interestingly, the shoot bud regeneration frequency of the phyA mutant was not significantly different from that of the wild-type in a light and dark , suggesting that phytochrome A may not be involved in the regulation of in-vitro shoot bud regeneration. The effects of gibberellin (GA) were also studied because previously we showed that a reduction in endogenous GA level results in a higher shoot bud regeneration frequency. Exogenous paclobutrazol and prohexadione (GA biosynthesis inhibitors) increases, and exogenous GA reduces, the shoot bud regeneration frequency in the phyB mutant. Thus shoot regeneration in the phyB mutant is still responsive to regulation via the GA signalling system.